2020
DOI: 10.3324/haematol.2020.247015
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: the (r)evolution of current therapy and a glance into future

Abstract: Over the past 20 years, the regulatory approval of several novel agents to treat multiple myeloma (MM) has prolonged median patient survival from 3 to 8-10 years. Increased understanding of MM biology has translated to advances in diagnosis, prognosis, and response assessment, as well as informed the development of targeted and immune agents. Here we provide an overview of the recent progress in MM, and highlight research areas of greatest promise to further improve patient outcome in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 151 publications
0
43
0
1
Order By: Relevance
“…Notably, in a IMiD-conditioned TME, T-cell activation is facilitated, as it no longer requires co-stimulation by antigen-presenting DCs [ 24 , 25 , 26 , 27 ]. In addition, IMiDs trigger caspase-mediated apoptosis in MM cells and impair their interaction with the protective BM stroma [ 28 ]. Efforts are underway to further enhance the clinical potency of IMiDs by combining them with modulators of cereblon E3-ligase, such as iberdomide, that accelerate IMiD-mediated degradation of IKZF1/IKZF3 [ 26 , 27 ].…”
Section: Immunomodulatory Imide Drugs (Imids) To Overcome the Immunosuppressive Tme In MMmentioning
confidence: 99%
“…Notably, in a IMiD-conditioned TME, T-cell activation is facilitated, as it no longer requires co-stimulation by antigen-presenting DCs [ 24 , 25 , 26 , 27 ]. In addition, IMiDs trigger caspase-mediated apoptosis in MM cells and impair their interaction with the protective BM stroma [ 28 ]. Efforts are underway to further enhance the clinical potency of IMiDs by combining them with modulators of cereblon E3-ligase, such as iberdomide, that accelerate IMiD-mediated degradation of IKZF1/IKZF3 [ 26 , 27 ].…”
Section: Immunomodulatory Imide Drugs (Imids) To Overcome the Immunosuppressive Tme In MMmentioning
confidence: 99%
“…11 Compromised immune component of the bone marrow niche including dysregulated regulatory T cells, myeloid derived suppressor cells, Th17 cells, tumor-associated macrophages, mesenchymal stromal cells, and osteoclasts confer immunosuppression and promote tumor immune escape; and therefore represents an ideal target for novel therapeutics. 12,13 Importantly, extensive research has shown the role of plasmacytoid dendritic cells (DCs) in promoting MM cell survival and drug resistance, 14 providing the framework for targeting plasmacytoid DCs/MM cells interaction in novel therapies. 15,16 Similarly, increased expression of immune checkpoints, ie PD-1/PD-L1, in T cells and MM cells, promotes tumor immune evasion and has been also associated to progression from precursor stages.…”
Section: Immune Dysfunction In MMmentioning
confidence: 99%
“…The exceptional sensitivity of MM plasma cells to PI is related to their heightened dependency on the protein quality control system due the high turnover of abnormal immunoglobulins. 12,24 PIs overwhelm proteasome load, increase the accumulation of misfolded and unfolded proteins, thus leading to endoplasmic reticulum stress and eventually cell death. 12 As proteins involved in several biological processes are substrate of the proteasome, its inhibition has multiple downstream effects, including decrease of cell proliferation and apoptosis induction, cell-cycle arrest, deficit in DNA repair mechanisms, and alteration of cellular metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An equally important yet tumor cellextrinsic driver of RRMM pathophysiology is the tumor microenvironment (TME), which provides myeloma-promoting interactions with resident BM cells, including specimens of the innate and adaptive immune system (8). Enhanced understanding of immune regulation of the BM microenvironment (BMME) has not only shed light on pathways of myeloma progression but also greatly advanced myeloma treatment over the past decade (9).…”
Section: Introductionmentioning
confidence: 99%